2020
DOI: 10.1029/2019jd032300
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and Modeling of Both Distant and Close Electric Fields of an M‐Component in Rocket‐Triggered Lightning

Abstract: Simultaneous measurements of current and multiple-station electric fields associated with a 5.4-kA-peak M-component in rocket-triggered lightning are presented in this study. A close-range electric field measurement site was located northeast of the triggering site, 195°clockwise from South, at a distance of 78 m, while the distant multiple stations in this study were located southwest of the lightning triggering site (25-48°, clockwise from South) at a distance ranging from 69 to 126 km. Both the fast microse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…A final remark is in order on the difficulty in distinguishing between the fast pulse resulting from the tall tower and the so-called microsecond-scale pulse associated with the junction process of in-cloud leaders and the grounded, current-carrying channel. Indeed, the fast microsecond-scale pulse which precedes the onset of the slow millisecond-scale pulse is very similar in shape to the sharp peak produced by a tall struck object (e.g., Azadifar et al, 2019;Q. Li et al, 2020).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…A final remark is in order on the difficulty in distinguishing between the fast pulse resulting from the tall tower and the so-called microsecond-scale pulse associated with the junction process of in-cloud leaders and the grounded, current-carrying channel. Indeed, the fast microsecond-scale pulse which precedes the onset of the slow millisecond-scale pulse is very similar in shape to the sharp peak produced by a tall struck object (e.g., Azadifar et al, 2019;Q. Li et al, 2020).…”
Section: Discussionmentioning
confidence: 91%
“…Instrumented towers (e.g., Azadifar et al., 2014, 2019; Guimaraes et al.,2014; Ishii et al.,2014; Paul & Heidler, 2019; Pavanello, Rachidi, Janischewskyj, et al., 2007; Pavanello, Rachidi, Rubinstein, et al., 2007; Pichler et al., 2010; Romero et al., 2010; Visacro et al., 2013; Zhou et al., 2011, 2015) have been used to obtain information on lightning currents and the associated electromagnetic fields. Experiments using rocket‐triggered lightning (e.g., Q. Li et al., 2020; Qie et al., 2011; Rakov, 2016, 1995; Thottappillil et al., 1995; Wang et al., 1999; Zhang et al., 2011) also constitute an important source of information to investigate the physics and characteristics of various stages in a lightning discharge, including subsequent return strokes and M‐components.…”
Section: Introductionmentioning
confidence: 99%
“…The true type test requires a large‐capacity impulse current generator and a wide test site, which can effectively simulate the actual lightning current discharge process of a single lightning strike. However, studies have shown that the lightning strike process generally includes several return strokes [12] and M‐components [13, 14]. The true‐type test also differs from the actual grounding grid impulse current dissipation characteristics.…”
Section: Introductionmentioning
confidence: 99%